Leaf/shoot level ecophysiology in two broadleaf and two needle-leaf species under representative cloud regimes at alpine treeline (2016)
Aims The effects of clouds are now recognized as critically important to the understanding of climate change impacts on ecosystems. Regardless, few studies have focused specifically on the ecophysiological responses of plants to clouds. Most continental mountain ranges are characterized by common convective cloud formation in the afternoons, yet little is known regarding this influence on plant water and carbon relations. Here we compare the ecophysiology of two contrasting, yet ubiquitous growth forms, needle-leaf and broadleaf, under representative cloud regimes of the Snowy Range, Medicine Bow Mountains, southeastern Wyoming, USA. Methods Photosynthetic gas exchange, water use efficiency, xylem water potentials and micrometeorological data were measured on representative clear, overcast and partly cloudy days during the summers of 2012 and 2013 for two indigenous broadleaf (Caltha leptosepala and Arnica parryi) and two needle-leaf species (Picea engelmannii and Abies lasiocarpa) that co-occur contiguously. Important Findings Reductions in sunlight with cloud cover resulted in more dramatic declines in photosynthesis for the two broadleaf species (ca. 50-70% reduction) versus the two conifers (no significant difference). In addition, the presence of clouds corresponded with lower leaf conductance, transpiration and plant water status in all species. However, the more constant photosynthesis in conifers under all cloud conditions, coupled with reduced transpiration, resulted in greater water use efficiency (ca. 25% higher) than the broadleaf species. These differences appear to implicate the potential importance of natural cloud patterns in the adaptive ecophysiology of these two contrasting, but common, plant growth forms.